Review of the Effectiveness of Enteral Feeding in Pediatric Oncology Patients. (November 2017) - Trimpe, Kaleena; Shaw, Michele R.; Wilson, Marian; Haberman, Mel R.
Enteral supplementation for nutritional support in pediatric oncology patients remains nonstandardized across institutions and between providers. Pediatric oncology patients frequently fail to meet their growth curve percentiles, lose weight, and/or are malnourished due to both the oncologic process as well as side effects from chemotherapy and radiation treatments. Methods of increasing weight include enteral feeding (nasogastric, nasoduodenal/jejunal, or gastrostomy), parenteral intravenous feeding, and oral supplementation. Indications for feeding and feeding protocols are highly variable, in part due to parental and familial choices, and in part due to the lack of guidelines available for providers. This article provides a comprehensive literature review of 8 published studies regarding the effectiveness and safety of enteral feeding in maintaining or increasing weight in pediatric oncology patients to help inform practice. The review concludes that enteral feeding in pediatric oncology patients is an effective and safe method to affect weight positively. However, further research is needed for developing treatment guidelines, including establishing a timeline for initiation of feeding, and determining which patients are most likely to benefit from enteral feeding.